An overview of osteoporosis and heath promotional strategies for community based osteoporosis prevention in Malaysia - Amin, Samia; Abdul Rahman, Hejar; Ismail, Suriani; Zainal Abidin, Emilia (Community Health Society Malaysia, 2017)
Osteoporosis is a global health problem which affects financial resources for prevention and treatment. It is generally a silent disease, undiagnosed until what would otherwise be a minor trauma from a fall causing a fracture, most commonly occurs at the hip, spine or wrist. It not only causes increase economic burden but also leads to social, physical and psychological consequences which expected to affect more people worldwide by 2050. It is no longer confined to the growing older population but has implications for all age groups. But with the progression of age, bone break down slowly over takes bone formation, resulting in gradual bone loss and more porous, osteoporosis is likely to occur. Such gradual change inevitably contribute progressively to morbidity. An inactive lifestyle, insufficient calcium intake, heavy smoking, excessive alcohol consumption, poor diet, menopausal woman, aged over 50, or have a family history of osteoporosis increase the risk of osteoporotic fractures. Osteoporosis is preventable with proper nutrition and lifestyle habits at the community level through health promotion & education which is effective in improving knowledge and awareness. So educating people on predisposing factors and symptoms of osteoporosis would be one of the best choice for increasing knowledge of osteoporosis inducing behavioural change in the period of peak bone density which is beneficial. Public awareness of osteoporosis remains low, especially in developing countries. So, heath promotional strategies for community based osteoporosis prevention in Malaysia is essential and recommended.